ANALISIS KINERJA KEUANGAN PADA TOKO MARHANI - Gusnawati Tonda; Ignasius Narew (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2022)
Gusnawati Tonda, Nim: 301302182150027, Measuring Financial Performance at Marhani Store. Lecturer of guidance Mr. Ignasius Narew, S.E, M.Ak, College of Economics Of The Moon Bridge. This research aims to find out the financial performance of Toko Marhani by using profitability, liquidity, and Economic Value Added (EVA) methods. The method used is a descriptive method. This study obtained primary data in the form of financial data owned by Toko Marhani. The results of Toko Marhani's research were concluded to have good financial performance from every measuring instrument used.